PRENATAL YOGA DAN KONDISI KESEHATAN IBU HAMIL - Islami Islami; Titik Ariyanti (Jurnal Ilmu Keperawatan dan Kebidanan, 2019)
Background: Pregnancy is a fisiologis process, but  midwifery care is needed by mother to evaluated that pregnancy. Midwife is a person who given midwifery care to improved the healthy pregnant.  During pregnancy, the body will be change that caused discomforted for mother and influenced several factor such us hormonal condition. Yoga is the one of activity that might do for all of people including pregnant woman. Yoga for pregnant or prenatal yoga can decrease physicly discomfort for pregnant mother and can made better feeling. The purposes is to measure relationship of prenatal yoga and maternal wellbeing.Methods: The research used pre and post data  designe. 30 pregnant were had participant by research. The population were taken in Budi luhur clinic Kudus district during 2017. Purposive sampling and marginal homogeneity test is used.Result: The research   obtained  maternal health condition before prenatal yoga  have one until three pregnancy complaints is 69% and 31% maternal have more than 3 pregnancy complaints. Mother who practiced prenatal yoga 58.6% didn’t have pregnancy complaints and 41% had one until three pregnancy complaints.  The statistic test marginal homogeneity  obtained p value 0.000.Conclusions: Prenatal yoga is relatively effective to decrease pregnancy complaints. Mother who practiced prenatal yoga during pregnancy less pregnancy complaints.Keywords: prenatal yoga, pregnancy complaints